2010
DOI: 10.1186/1471-2296-11-48
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity of Estonian family doctors and their counselling for a healthy lifestyle: a cross-sectional study

Abstract: BackgroundPhysical activity offers major health benefits and counselling for it should be integrated into the medical consultation. Based on the literature, the personal health behaviour of the physician (including physical activity) is associated with his/her approach to counselling patients. Our hypothesis is that family doctors (FD) in Estonia are physically active and their recommendation to counsel patients with chronic diseases to use physical activity is high. The study was also interested in how FDs va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
65
1
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 14 publications
7
65
1
4
Order By: Relevance
“…Other researchers have found similar correlation between depression and physical activity in their surveys [14,15]. Table 3.…”
Section: M-arithmetic Mediana Sd-standard Deviation Se-standard Errorsupporting
confidence: 65%
See 1 more Smart Citation
“…Other researchers have found similar correlation between depression and physical activity in their surveys [14,15]. Table 3.…”
Section: M-arithmetic Mediana Sd-standard Deviation Se-standard Errorsupporting
confidence: 65%
“…The study on correlation between physical activity and lifestyle conducted in Estonia showed that 92% of interviewed female family doctors do moderate to vigorous physical activity and that the level of physical activity was not related to age, BMI, living area and time they spent sitting [14]. The survey that compared BMI, blood pressure and waist circumference with the level of physical activity, using IPAQ among students in Brazil found sedentary lifestyle in 52% of students.…”
Section: M-arithmetic Mediana Sd-standard Deviation Se-standard Errormentioning
confidence: 99%
“…In contrast, higher levels of compliance with PA guidelines (92%) were found among a sample of female Estonian physicians. 35 Although these differences may reflect genuine gender differences, i.e., women physicians tend to have better healthy habits than men, the use of different questionnaires or differences in the Health care systems make it difficult to compare between studies. These data confirm that, like physicians from other countries, Catalan physicians comply with the general PA recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The study on correlation between physical activity and lifestyle conducted in Estonia showed that 92% of interviewed female family doctors did moderate to vigorous physical activity and that the level of physical activity was not related to age, BMI, living area and time they spent sitting (Suija, Pechter, Maaroos, Kalda, Ratsep, Oona, & Maaroos, 2010).…”
Section: Phq-9 Score ≤4 (No Depression)mentioning
confidence: 98%